Saving creation: nature and faith in the life of Holmes Rolston III (review) - Bouma-Prediger, Steven, author; Union Presbyterian Seminary, publisher (Colorado State University. Libraries, 2010)
Preston engagingly tells the story of Rolston, from his childhood in the Shenandoah Mountains, to his long and distinguished career as a philosopher at Colorado State University. As the story of a human life, it is an interesting read, but along the way, Preston also adroitly interweaves the story of the rise and development of environmental ethics as an academic discipline. This is an impressive work overall. If you are interested in natural science and Christian theology, this is a book for you. If you are interested in environmental ethics, this is a book for you. Or, if you are just interested in a fascinating human story, well told, this is a book for you.
Keywords: environmental ethics; Colorado State University; Rolston, Holmes, 1932-2025; science and religion; intellectual biography